2018
DOI: 10.35808/ersj/1070
|View full text |Cite
|
Sign up to set email alerts
|

Impersonal Trust and Perceived Organizational Politics on Organizational Commitment

Abstract: This study aims to analyze the role of impersonal trust in moderating the influence of perceived organizational politics on organizational commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Several previous studies reported diverse negative effects of the perceptions of organizational politics; the perceptions can lead to less organizational commitment of members, which is one of the negative results (De Clercq et al, 2023;Cropanzano et al, 1997;Kimura, 2013;Nurhayati et al, 2018;Vigoda-Gadot and Talmud, 2010;Witt et al, 2002). Organizational commitment refers to members' positive attitudes toward the organization, including psychological attachment, identification, involvement, and sense of obligation (Meyer and Allen, 1987;Mowday et al, 1979).…”
Section: Perceptions Of Organizational Politics and Organizational Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies reported diverse negative effects of the perceptions of organizational politics; the perceptions can lead to less organizational commitment of members, which is one of the negative results (De Clercq et al, 2023;Cropanzano et al, 1997;Kimura, 2013;Nurhayati et al, 2018;Vigoda-Gadot and Talmud, 2010;Witt et al, 2002). Organizational commitment refers to members' positive attitudes toward the organization, including psychological attachment, identification, involvement, and sense of obligation (Meyer and Allen, 1987;Mowday et al, 1979).…”
Section: Perceptions Of Organizational Politics and Organizational Co...mentioning
confidence: 99%
“…, 2023; Cropanzano et al. , 1997; Kimura, 2013; Nurhayati et al. , 2018; Vigoda-Gadot and Talmud, 2010; Witt et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation